Conservation Text As an Indonesian Course Teaching Material: Conservation-Based Curriculum Innovation - Yuniawan, Tommi; Rokhman, Fathur; ., Rustono; Retnoningsih, Amin (KnE Social Sciences, 2019)
Conservation texts meet the expression of the language upon which conservation events are presented related to the university’s vision (UNNES) of conservation. In the conservation text, there is a language expression of being environment-friendly and noble character values. Theoretically, the interrelations between environment and language are studied in ecolinguistics. This study aims to describe the form of conservation text as a teaching material of the Indonesian general course as an innovative conservation-based curriculum. This research employed ecolingustics design. The data collection was done through several methods including book study and documentation. The analysis of the data used distributional and referential methods. The conservation text can be used as teaching material of general course of Indonesian Language on forms of: (1) news text (2) regulation text, (3) literary text, (4) songtext/lyric,(5)comictext,and(6)slogantext.Inaddition,inthe conservationtextit can be identiﬁed also its functions, namely: (1) to inform, (2) to provide legal umbrella, (3)tocriticize,(4)toentertain,and(5)toencourage.Theresultsofthisstudycontribute to the nature of Indonesian course teaching material based on conservation and also contribute in the ﬁeld of language learning. Keywords: Ecolinguistics, Conservation-Based Curriculum, Indonesia General course, Conservation Text